Fictibacillus enclensis sp nov., isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Srinivasan, Krishnamurthi; Tang, Shan-Kun; Lee, Jae-Chan; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel Gram-positive strain, designated NIO-1003(T), was isolated from a marine sediment sample collected from the Chorao Island, Goa Provence, India. Strain NIO-1003(T) was found to be strictly aerobic, motile, endospore-forming rods. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1003(T) belongs to the genus Fictibacillus and to be most closely related to Fictibacillus rigui KCTC 13278(T), Fictibacillus solisalsi KCTC 13181(T) and Fictibacillus barbaricus DSM 14730(T) with 98.2, 98.0 and 97.2 % similarity and 25, 28, 39 nucleotide differences respectively. Strain NIO-1003(T) was characterized by having cell-wall peptidoglycan based on meso-diaminopimelic acid and MK-7 as the predominant menaquinone. The polar lipid profile exhibited the major compounds diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. In addition, minor amounts of an aminophospholipid were detected. The major fatty acids were identified as ai-C-15:0, iso-C-15:0, ai-C-17:0 and C-16:0, supporting the grouping of strain NIO-1003(T) into the family Bacillaceae. The DNA G+C content of strain NIO-1003(T) was determined to be 42.6 mol%. On the basis of phenotypic properties, phylogeny and DNA-DNA hybridisation analysis, strain NIO-1003(T) is considered to represent a novel species of the genus Fictibacillus for which the name Fictibacillus enclensis sp. nov. is proposed. The type strain is NIO-1003(T) (= NCIM 5458(T) = DSM 25142(T)).
Keywords: Chorao Island; Fictibacillus sp.; Polyphasic taxonomy